PENGARUH EPS, PER, DER, ROE TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2010-2012 - Dorothea Ratih; Apriatni Endang Prihatini; Saryadi Saryadi (Universitas Diponegoro, 2014)
One source of funds obtained by the company is derived from the sale of shares. Stock price changes up or down time by time, and it is influenced by many factors. This research was conducted to examine the effect of Earning Per Share (EPS), Price Earning Ratio (PER), Debt To Equity Ratio (DER), Return on Equity (ROE) on stock price in the Mining Sector Listed in Indonesia Stock Exchange (IDX) in the period 2010-2012.The data used in this research is a secondary data obtained from Indonesia Stock Exchange. The analysis technique using linear regression, while hypothesis testing using t-test and test-F at a significance level of 5%. The classical assumptions test used in this reasearch include normality, multicolinearity, heteroscedasticity and autocorrelation test.Based on the research result that the Earning Per Share (EPS), Price Earning Ratio (PER), and Return On Equity (ROE) and a significant positive effect on Stock Price. Meanwhile, Debt To Equity Ratio (DER) has negative affect on the stock price. Simoultaneously there is a significant effect between Earning Per Share, Price Earning Ratio, Debt To Equity Ratio, dan Return On Equity to the Stock Price.For investors who want to invest stocks, should pay attention to the level of Earning Per Share too, as in this research say that Earning Per Share provides the most powerful influence on Stock Price.